Exploring the potential benefits of areca nut extract in animal production: a review - Liu, Zhuying; Wang, Xiaolong; Wen, Lixin (Frontiers in Animal Science, 2025)
Globally, the issue of antibiotic residues in agricultural products and their environments is increasingly critical, with the spread of microbial resistance becoming an urgent international challenge. Therefore, the development of ecological health feed additives is of paramount importance for advancing sustainable animal husbandry. Areca nut extract, derived from commonly available food sources, has garnered attention due to its exceptional bioactive properties. Its remarkable anti-inflammatory and antioxidant potential, along with its outstanding performance in antibacterial, antifungal, and antiviral activities, plays a crucial role in inhibiting various pathogens and protecting cells from oxidative damage. This review aims to comprehensively explore the biological activities of areca nut extract and delve into its practical application potential in enhancing animal production efficiency and promoting sustainable livestock development.The pervasive presence of antibiotic residues—including tetracyclines, sulfonamides, and quinolones—in agricultural products such as meat, milk, and eggs has raised significant concerns due to their extensive use in animal husbandry. This issue is not only a formidable challenge for food safety but also exacerbates the global crisis of antimicrobial resistance (AMR). To address these challenges, there is an urgent need for safe and sustainable alternatives to antibiotics in animal production. Among these alternatives, plant extracts have garnered considerable attention for their natural bioactive properties. Notably, areca nut extract has emerged as a promising candidate due to its diverse biological activities and potential applications in livestock production.Areca nut, derived from the dried ripe fruits, seeds, peels, and flowers of Areca catechu, is well-documented in traditional medicine sources such as the Pharmacopoeia of the People’s Republic of China (2010 Edition) for its medicinal properties, including antiparasitic effects, digestive support, and antimicrobial activity. This review focuses on the biological activities of areca nut extract, particularly its antioxidant, anti-inflammatory, antiparasitic, antibacterial, and microbiota-modulating effects, which collectively contribute to its potential role as a feed additive for enhancing animal health and performance.Key findings indicate that areca nut extract can promote livestock productivity by accelerating growth, enhancing immune responses, and reducing disease incidence. Additionally, its biological properties show potential for improving feed efficiency and mitigating the environmental footprint of livestock operations. By exploring these activities, we aim to provide theoretical insights and practical guidance for the application of areca nut extract in animal husbandry.This review highlights the promise of areca nut extract as a natural, effective, and sustainable alternative to antibiotics, offering solutions to the pressing issues of antibiotic residues and AMR. Its potential contributions to sustainable livestock production underscore the importance of further scientific exploration and interdisciplinary collaboration in this field.